Association of antinuclear antibody positivity with liver disease severity in pediatric metabolic dysfunction-associated steatotic liver disease - Kim, Hyun Jin; Kim, Ju Young; Lee, Yoo Min; Hong, Yong Hee; Kang, Ben; Choe, Byung-Ho; Yi, Dae Yong; Lee, Eun Hye; Kim, Soon Chul; Choi, You Jin; Jang, Hyo-Jeong; Choi, So Yoon (Frontiers in Pediatrics, 2025)
BackgroundAlthough antinuclear antibody (ANA) is frequently observed in patients with metabolic dysfunction-associated steatotic liver disease (MASLD), its clinical significance in children remains unclear and controversial. In this study, we investigated the prevalence of ANA positivity and the factors associated with it in pediatric MASLD patients without concurrent autoimmune hepatitis.MethodsWe retrospectively reviewed the medical records of patients aged 4–18 years diagnosed with MASLD and tested for ANA from January 2015 to December 2020 at 10 hospitals in Korea. All statistical analyses were carried out using SPSS 26.0 and P-values <0.05 were considered statistically significant.ResultsOut of the 439 patients included, ANAs were present in 89 (20.3%); 51 (57.3%) patients had ANA titer <1:80; 22 (24.7%), <1:160; 10 (11.2%), <1:320; and 6 (6.7%), <1:640. Compared to ANA-negative patients, aspartate aminotransferase (AST, P = 0.003) and alanine aminotransferase (ALT, P = 0.007) levels were significantly higher in ANA-positive patients. The ALT to Platelet Ratio Index (APRI) score was also associated with the ANA-positive patients (P = 0.005). To predict ANA positivity using APRI, the area under receiver operating characteristic (AUROC) curve was 0.597 (p = 0.004), and the APRI cutoff value of >0.893 could predict ANA, with sensitivity and specificity of 42.7% and 72.9%, respectively.ConclusionsANA positivity in pediatric MASLD is associated with greater liver enzyme elevation and increased risk of fibrosis, highlighting the need for careful monitoring in ANA-positive patients.